Oxford-AstraZeneca Coronavirus Disease-2019 Vaccine-Induced Immune Thrombocytopenia on Day Two - Azhar Kareem Razzaq; Ameer Al-Jasim (Case Reports in Hematology)
Introduction. Vaccines have been one of the most impactful human discoveries that have significantly changed life expectancy. Immune thrombocytopenic purpura (ITP) is an autoimmune disease characterized by platelet damage, life-threatening thrombocytopenia, and haemorrhage when the platelet count reaches below 20 × 109/mcL. Its pathogenesis involves viral mimicry or T-cell-induced immune destruction in antibody-negative cases. The clinical manifestations of thrombocytopenia vary according to the severity (level of platelets) and range from being asymptomatic to severe haemorrhage. ITP is treated with immunosuppression. Case Presentation. A 26-year-old Iraqi male laboratory analyst with an unremarkable medical history presented with severe thrombocytopenia 2 days after receiving the Oxford-AstraZeneca coronavirus disease-2019 vaccine. The patient was asymptomatic with unremarkable examination findings. However, his low platelet count was discovered accidentally, and the patient did not exhibit the resistance pattern of ITP and recovered successfully with regular immunosuppressant treatment. Conclusion. Patients with a history of thrombocytopenia can develop vaccine-induced thrombocytopenia earlier than the expected onset. Close monitoring, through regular complete blood counts, is highly recommended for patients with previous thrombocytopenia because the immune modulation process of the vaccine can worsen preexisting thrombocytopenia.